Children, adolescents, and media violence a critical look at the research - Kirsh, Steven J.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
Kirsh provides a review and critique of the literature related to media violence in all its forms during childhood and adolescence. Special attention is paid to evaluating the role of the development processes in media violence research and to stressing the importance of methodology in understanding that research.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mass media and children; Mass media and teenagers; Children and violence; Youth and violence; Violence in mass media; Aggressiveness in children; Aggressiveness in adolescence; Electronic books